Yushak V. M. Сomparative analysis of anthroponyms-symbols translation and speaking personal names - Yushak V. M. (Philological Treatises, 2020)
The article deals with the transfer of personal names from English into Ukrainian. Possible ways of translation of anthroponyms-symbols and speaking names are analyzed.